2003
DOI: 10.1128/jb.185.4.1181-1189.2003
|View full text |Cite
|
Sign up to set email alerts
|

CDP-2,3-Di -O- Geranylgeranyl- sn -Glycerol: l -Serine O -Archaetidyltransferase (Archaetidylserine Synthase) in the Methanogenic Archaeon Methanothermobacter thermautotrophicus

Abstract: thermautotrophicus genome annotated as the gene encoding phosphatidylserine synthase was found to be homologous to Bacillus subtilis pssA but not to Escherichia coli pssA. The substrate specificity of phosphatidylserine synthase from B. subtilis was quite similar to that observed for the M. thermautotrophicus archaetidylserine synthase, while the E. coli enzyme had a strong preference for CDP-1,2-diacyl-sn-glycerol. It was concluded that M. thermautotrophicus archaetidylserine synthase belongs to subclass II p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
(38 reference statements)
0
31
0
Order By: Relevance
“…The biosynthetic intermediates of ether polar lipids in archaea include geranylgeranyl ether lipids, which are a kind of allyl ethers. [78][79][80][81] If a stable saturated ether bond is essential for survival at high temperatures and unstable allyl ether bonds are degraded at those temperatures, the organism cannot survive at high temperatures because a trace amount of the unstable allyl ether intermediates would be degraded and the stable lipid could not be synthesized at high temperatures. It can, therefore, be concluded that stable ether bonds are not a result of adaptation to hot environments.…”
Section: Physiological Significance Of Archaeal Lipids-what Is a mentioning
confidence: 99%
“…The biosynthetic intermediates of ether polar lipids in archaea include geranylgeranyl ether lipids, which are a kind of allyl ethers. [78][79][80][81] If a stable saturated ether bond is essential for survival at high temperatures and unstable allyl ether bonds are degraded at those temperatures, the organism cannot survive at high temperatures because a trace amount of the unstable allyl ether intermediates would be degraded and the stable lipid could not be synthesized at high temperatures. It can, therefore, be concluded that stable ether bonds are not a result of adaptation to hot environments.…”
Section: Physiological Significance Of Archaeal Lipids-what Is a mentioning
confidence: 99%
“…In addition, electron impact-mass spectrometry of the first main peak gave a signal of m/z 633 (M-CH 3 ) ϩ , which is consistent with the molecular weight of IP(TMS) 5 Me 2 . The second and third main peaks were confirmed to be glucose 6-phosphate(TMS) 4 Me 2 by electron impact-mass spectrometry (m/z 561 (M-CH 3 ) ϩ ). Thus, the product of the IP synthase reaction was decisively determined to be 1L-myo-inositol 1-phosphate.…”
Section: Resultsmentioning
confidence: 98%
“…The precipitated protein was removed by centrifugation, and the supernatant was incubated at 37°C for 1 h with 0.2 M NaIO 4 . Then 1 M Na 2 SO 3 was added to destroy excess NaIO 4 , and liberated P i was measured using the method of Barnett (21). The net P i value was obtained by subtraction of the blank value of the reaction mixture that received Na 2 SO 3 before the addition of NaIO 4 .…”
Section: Materials-␤-d-glucosementioning
confidence: 99%
See 2 more Smart Citations